Portrait of the Palliative Needs of an Internal Medicine Service of a Tertiary Hospital in Portugal - Moura de Azevedo, Sofia (2023)
Introduction: The clinical profile of patients admitted to Internal Medicine services is characterized by increasing frailtyand complexity. The main objective of this study was to determine the prevalence of palliative care needs in an InternalMedicine Service using the NECPAL instrument. Material and Methods: An institutional, clinical, descriptive,observational and cross-sectional study was conducted. Of the 148 patients admitted to the Internal Medicine Service of a tertiary hospital on 20th April of 2022, 122 patients presentedeligibility criteria for application of the NECPAL inquiry by health professionals (doctors and nurses). Statistical analysiswas performed in SPSS® version 26 software. Results: The prevalence of palliative needs in this InternalMedicine Service was 88.5% (n = 108). Of these, 72.2 % (n =78) were in stage 3 prognosis of NECPAL, whose median survival is 3.6 months. Most healthcare professionals (56.9%, n = 29) had no basic training in palliative care. Nurses and physicians were concordant in most of their assessments regarding the surprise question, differing in 27.9% (n = 34) of patients, and in all of these the prognosis-defining disease was non-oncologic. Discussion/Conclusion: The palliative needs in this InternalMedicine Service are high, possibly portraying the nationalreality. Giving visibility to the needs of our population isimperative for better management of individual care, humanresources and creation of government plans.